Economic case for migration restrictions in Europe - TOPORNIN, N; SHMIDT, Y.; SEREGINA, T.; BRATANOVSKII, S. (Utopía y Praxis Latinoamericana, 2019)
ABSTRACT The article concentrates on immigration and emigration impact on EU Member State economy and analyzes the migration situation in Poland. If the purpose of immigration is to obtain a residency and then integration into society, thus the increase in population will be adopted by the national economy in a short period. There also won’t be problems with circular migration, since the workforce rotation will be within the agreed limits. However, temporary migration will lead either to unacceptably low living conditions of temporarily employed foreigners, to an increase in social tension, or to an inefficient use of social infrastructure.RESUMEN El artículo se centra en el impacto de la inmigración y la emigración en la economía de los Estados miembros de la UE y analiza la situación de la migración en Polonia. Si el propósito de la inmigración es obtener una residencia y luego la integración en la sociedad, el aumento de la población será adoptado por la economía nacional en un corto período. Tampoco habrá problemas con la migración circular, ya que la rotación de la fuerza laboral estará dentro de los límites acordados. Sin embargo, la migración temporal conducirá a condiciones de vida inaceptablemente bajas de extranjeros empleados temporalmente, a un aumento de la tensión social o al uso ineficiente de la infraestructura social.